Internet connectivity disruption in Angola (Angola) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Angola. Data sourced from IODA.
Network Disruption Incident ID: AO-2026-0033. Severity: critical. Confidence: 67%